2017
DOI: 10.3389/fimmu.2017.01791
|View full text |Cite
|
Sign up to set email alerts
|

The CD40–CD40L Dyad in Experimental Autoimmune Encephalomyelitis and Multiple Sclerosis

Abstract: The CD40–CD40L dyad is an immune checkpoint regulator that promotes both innate and adaptive immune responses and has therefore an essential role in the development of inflammatory diseases, including multiple sclerosis (MS). In MS, CD40 and CD40L are expressed on immune cells present in blood and lymphoid organs, affected resident central nervous system (CNS) cells, and inflammatory cells that have infiltrated the CNS. CD40–CD40L interactions fuel the inflammatory response underlying MS, and both genetic defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 117 publications
(140 reference statements)
2
55
0
Order By: Relevance
“…These data suggest that genetically-determined modulation of CD40 mRNA expression may promote MS risk via effects of alternatively-spliced transcripts on IL-10 production, although the exact mechanism remains to be clarified. Monoclonal antibodies blocking the interaction between CD40L and CD40 have shown efficacy in rodent and primate EAE 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that genetically-determined modulation of CD40 mRNA expression may promote MS risk via effects of alternatively-spliced transcripts on IL-10 production, although the exact mechanism remains to be clarified. Monoclonal antibodies blocking the interaction between CD40L and CD40 have shown efficacy in rodent and primate EAE 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Early phase II data showed promising efficacy of an anti-CD40L mAb in lupus nephritis 27 . Despite phase I safety of the anti-CD40L antibody, IDEC-131, in MS, the phase II trial was halted due to increased risk of thromboembolic disease caused by inhibition of the thrombusstabilising interaction between CD40L and platelet alpha2,beta3 integrins 24,28 . Subsequently, various strategies have been deployed to overcome this safety concern.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, CD49d + CD154 + lymphocyte proliferation was accompanied by enhanced concentration of sCD40 in supernatants as a result of negative feedback regulatory loop for CD154-CD40 interaction ( Figure 1C) [26]. RR-MS PBMCs in response to myelin peptides opposite to HC PBMCs produced proinflammatory chemokines: CCL1, 2,7,8,20,21,22,24,25,27,CXCL1,2,5,6,8,9,11,17, proinflammatory cytokines: MIF1, IL-1β, IL-2, and TNF-α (Table 1). Taken together, we demonstrated the induction of autoreactive CD49d + CD154 + lymphocytes in MS patients in PBMCs exposed to myelin peptides and confirmed the role of CD154-CD40 interaction in this process.…”
Section: Cd49d + Cd154 + Lymphocytes Of Rr-ms Patients Proliferate Inmentioning
confidence: 99%
“…In a mouse model of RR-MS, experimental autoimmune encephalomyelitis (EAE), it was demonstrated that CD154 + T cells infiltrate the CNS on the fourth day of postimmunization and their number increases during the acute phase and remains constant in the period of remission [8]. CD154-mediated activation of CD40-expressing cells in the CNS such as monocytes, macrophages, and activated microglia [7] results in the secretion of proinflammatory cytokines/chemokines, which fuel ongoing inflammation [9]. The significance of CD154-CD40 dyad in the disease progression has been demonstrated in the studies with CD154 and CD40 knock-out mice, as well as with the use of neutralizing mAbs anti-CD154 or anti-CD40 in EAE [7,[10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation